2016
DOI: 10.1186/s12876-016-0549-6
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic influence of body mass index, resting energy expenditure and fasting blood glucose on postoperative patients with esophageal cancer

Abstract: BackgroundBody mass index (BMI), resting energy expenditure (REE) and fasting blood glucose (FBG) are major preoperative assessments of patients’ nutrition and metabolic state. The relations and effects of these indices on esophageal cancer patients’ postoperative short-term and long-term outcomes remain controversial and unclear. We aimed to study the impact of BMI, REE and FBG in esophageal cancer patients undergoing esophagectomy.MethodsThree hundred and six esophageal cancer patients who underwent esophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…A more pronounced decline in REE in very old subjects could even be a marker of frailty and sarcopenia as suggested by the results of a recent study [56]. In patients with esophageal cancer, not only was the REE not increased [57], but a low REE was also associated with worse survival at five years [58].…”
Section: Discussionmentioning
confidence: 92%
“…A more pronounced decline in REE in very old subjects could even be a marker of frailty and sarcopenia as suggested by the results of a recent study [56]. In patients with esophageal cancer, not only was the REE not increased [57], but a low REE was also associated with worse survival at five years [58].…”
Section: Discussionmentioning
confidence: 92%
“…carried out a prospective cohort study with 387 stage I-IV NSCLC patients and found that patients with a low FBG (<4 mmol/L) had a significantly higher risk of death than those with a high FBG [23]. Wu et al conducted a study that included 306 stage 0-III esophageal cancer patients who underwent esophagectomy and found that low postoperative FBG was related to poor survival, and an FBG ≤4 mmol/L was independently linked to poor survival [16]. In our study, we selected patients without a background of a prior preoperative aberrant FBG and found that a low postoperative FBG (<5.11 mmol/L) was associated with poor survival for CRC, which was partially consistent with the results of these studies [16,23].…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al conducted a study that included 306 stage 0-III esophageal cancer patients who underwent esophagectomy and found that low postoperative FBG was related to poor survival, and an FBG ≤4 mmol/L was independently linked to poor survival [16]. In our study, we selected patients without a background of a prior preoperative aberrant FBG and found that a low postoperative FBG (<5.11 mmol/L) was associated with poor survival for CRC, which was partially consistent with the results of these studies [16,23]. Notably, we also found that 58.75% (47/80) of patients maintained a relatively high FBG compared to their preoperative value at the 3-6 m follow-up, but FBG failed to present any prognostic value for DFS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutritional status is thought to be a prognostic factor for esophageal cancer patients. 4) In addition, low serum albumin 5) and high C-reactive protein (CRP) 6) are reported to be the significant predictors of poor prognosis in such patients. Conflicting reports have proposed a prognostic role of body mass index (BMI) for histologic types of esophageal cancer.…”
Section: Introductionmentioning
confidence: 99%